Analisis Respons Struktur Flat Slab-Drop Panel terhadap Beban Lateral pada Basement Bangunan Rumah Sakit - Hafiz, Dhamar Abu; Idroes, Imransyah; Hady, Munirul; Bunyamin, Bunyamin; Pramanda, Heru; Munirwan, Reza Pahlevi (Universitas Iskandar Muda, 2026)
Floor slabs are a primary component in building structural systems, typically comprising slabs, beams, and columns. However, advances in construction technology have enabled the adoption of flat slab systems, where slabs are directly supported by columns with or without thickening elements (drop panels), offering spatial efficiency and construction simplicity. The key issue addressed in this study is the influence of drop panels on structural response, particularly under lateral loading in basement structures. This study aims to evaluate the behavior of flat slab systems with and without drop panels subjected to lateral loads in the Cempaka Lima General Hospital building, Banda Aceh, Indonesia. The methodology involves the collection of primary data, including field measurements and building coordinates, as well as secondary data such as regional maps, seismic hazard maps, and as-built drawings. Structural analysis was conducted by comparing the response of both systems under earthquake loading using the time history method. The results indicate that the structure with drop panels exhibits a higher maximum axial force of 29,564.37 kN compared to 20,714.64 kN in the system without drop panels. The highest base shear values were also observed in the structure with drop panels, reaching 8,221.75 kN in the X direction and 8,112.79 kN in the Y direction. Displacement increased with the inclusion of drop panels, from 0.244 mm to 0.495 mm in the X direction and from 0.564 mm to 0.928 mm in the Y direction. Nevertheless, inter-story drift remained within the allowable limit of 2% as specified in SNI 1726:2019. These findings suggest that the use of drop panels enhances structural capacity against lateral loads; however, the associated increase in deformation must be carefully considered in practical design applications.